Three lessons on diabetes for global health professionals, researchers and policy-makers from the people of Ga Mashie - Sanuade, Olutobi Adekunle; Okoibhole, Lydia O.; Dankyi, Ernestina K.; Strachan, Daniel; Baatiema, Leonard; Kushitor, Sandra Boatemaa; Awuah, Raphael B.; Kushitor, Mawuli K.; Amon, Samuel; Kretchy, Irene Akwo; Arhinful, Daniel; Fottrell, Edward; et al. (Frontiers in Nutrition, 2025)
BackgroundDiabetes is a leading cause of death globally, with significant burdens in low- and middle-income countries (LMICs). However, knowledge of contextual factors associated with diabetes in LMICs are limited. This study highlights three important lessons on diabetes by identifying and interpreting contextual factors related to its prevention and management within a low-income urban community in Accra, Ghana.MethodsThis was a qualitative study. Data were collected through four focus group discussions (FGDs) with older adults men and women (50+ years) and 18 in-depth interviews with community stakeholders, including traditional leaders, market women, and the Ga Mashie Development Agency. Thematic analysis was conducted to identify key insights on diabetes perceptions, challenges, and cultural practices.ResultsThree key themes emerged from the data: (1) Knowledge does not always translate to action. While participants had extensive knowledge of diabetes risk factors and management, they cited practical constraints that hindered their ability to make behavior changes; (2) Food is more than nutrition. Participants noted that food plays an important role in family, community, and emotional well-being, and (3) Diabetes carries dual meanings. Participants associated diabetes with both individual lifestyle behaviors (e.g., alcohol consumption and sexual activity) and broader environmental exposures (e.g., pollution and chemical contaminants in food).ConclusionThese results highlight the complexity of diabetes management in an urban poor community context, requiring more than knowledge on diabetes risk factors for behavior change. Addressing personal, communal, and environmental factors, alongside structural barriers, is essential for developing effective, sustainable diabetes management strategies in this setting.